Estimating the costs of adolescent HIV care visits and an intervention to facilitate transition to adult care in Kenya. - Enrique M Saldarriaga; Kristin Beima-Sofie; Dalton Wamalwa; Cyrus Mugo; Irene Njuguna; Alvin Onyango; Grace John-Stewart; Monisha Sharma (PLoS ONE, 2024)
Introduction Adolescents with HIV in sub-Saharan Africa face challenges transitioning to adult HIV care, which can affect long-term HIV care adherence and retention. An adolescent transition package (ATP) focused on transition tools can improve post-transition clinical outcomes, but its implementation costs are unknown. Methods We estimated the average cost per patient of an HIV care visit and ATP provision to adolescents. Data was collected from 13 HIV clinics involved in a randomized clinical trial evaluating ATP in western Kenya. We conducted a micro-costing and activity-driven time estimation to assess costs from the provider perspective. We developed a flow-map, conducted staff interviews, and completed time and motion observation. ATP costs were estimated as the difference in average cost for an HIV care transition visit in the intervention compared to control facilities. We assessed uncertainty in costing estimates via Monte Carlo simulations. Results The average cost of an adolescent HIV care visit was 29.8USD (95%CI 27.5, 33.4) in the standard of care arm and 32.9USD (95%CI 30.5, 36.8) in the ATP intervention arm, yielding an incremental cost of 3.1USD (95%CI 3.0, 3.4) for the ATP intervention. The majority of the intervention cost (2.8USD) was due ATP booklet discussion with the adolescent. Conclusion The ATP can be feasibly implemented in HIV care clinics at a modest increase in overall clinic visit cost. Our cost estimates can be used to inform economic evaluations or budgetary planning of adolescent HIV care interventions in Kenya.